PEMBANGKIT GRUP PERSAMAAN SCHRODINGER - Aloysius Joakim Fernandez (Jurusan Matematika FMIPA Universitas Jenderal Soedirman, 2018)
In this article contains the Group’s concepts in mathematical analysis namely self-adjoint property and Stone Theorem. This theorem talks about generator infinitesimal of Group. Moreover, this article will discuss the concepts of Group in Schrodinger equation.